2004
DOI: 10.1007/s10350-003-0054-1
|View full text |Cite
|
Sign up to set email alerts
|

Colorectal Adenoma Characteristics as Predictors of Recurrence

Abstract: Follow-up colonoscopies in patients with adenomas should include careful examination of the proximal colon. The time interval between follow-up examinations could probably be extended beyond three years in patients who have only one or two distal adenomas.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
91
3
10

Year Published

2005
2005
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 127 publications
(110 citation statements)
references
References 33 publications
6
91
3
10
Order By: Relevance
“…Some studies have found that a proximal colon location indicates a high risk of recurrence (15). However, some of the above findings have not been borne out by larger studies.…”
Section: Discussionmentioning
confidence: 94%
“…Some studies have found that a proximal colon location indicates a high risk of recurrence (15). However, some of the above findings have not been borne out by larger studies.…”
Section: Discussionmentioning
confidence: 94%
“…Among patients that have had colorectal adenomas, recognized predictors of subsequent lesions include age, adenoma size, histology and multiplicity of the lesions at detection 1 . Depending on the age of the population, between 20 and 50% of those patients with adenomas will recur within a 3-5 year period, with 10-20% of recurrent lesions possessing clinically advanced features (larger size, villous histology, and/or high-grade dysplasia) [2][3][4][5][6] . The current recommendation for patients presenting with small polyps (less than 1 cm) is to have a followup colonoscopy 5-10 years after the initial procedure 1 .…”
Section: Introductionmentioning
confidence: 99%
“…It should be pointed out, however, that the definition of ACRC varies in the literature. Some authors regard as ACRC those adenomas measuring >1cm in diameter [20,21], others >1cm in diameter with villous histology [22][23][24]; others require the presence of HGD [25][26][27]; others, at least 1 cm or with villous elements at a frequency greater than 20% or with HGD [28]; and others as carcinoma in situ (intraepithelial carcinoma, IEC) [29][30][31]. Finally, some authors require the presence of in tramucosal carcinoma (IMC) [19,[32][33][34].…”
Section: Introductionmentioning
confidence: 99%